A new Potamocypridini genus of Cypridopsinae (Crustacea, Ostracoda) from Thailand, with a discussion on taxonomic characters and morphological evolution in the tribe - Savatenalinton, Sukonthip (Zootaxa, 2024)
A new genus and species belonging to the subfamily Cypridopsinae, Neopotamocypris indivisa gen. nov. sp. nov., is described from Thailand. The new genus is the second one of the tribe Potamocypridini. Neopotamocypris gen. nov. is similar to Potamocypris but can be distinguished mainly by the undivided penultimate segment of the second thoracopod, the absence of the d1 seta on the third thoracopod and the morphology of the mandibular palp, maxillula and female genital hook. The discovery of the new genus suggests the morphological divergent evolution at generic level within the tribe and also perhaps constitutes an example of convergent evolution in the subfamily. The taxonomic characters of the tribe are briefly discussed.